The hemodynamic effect of right ventricle (RV), RT3DE targeted left ventricle (LV) and biventricular (BIV) pacing in the early postoperative period after cardiac surgery - Straka, Frantisek; Pirk, Jan; Pindak, Marian; Skalsky, Ivo; Vancura, Vlastimil; Cihak, Robert; Marek, Tomas; Lupinek, Petr; Masin, Jaroslav; Schornik, David; Zeman, Michal; Skrobakova, Janka; et al. (Pacing and clinical electrophysiology, 2011)
BACKGROUND: Congestive heart failure negatively impacts the prognosis in patients after cardiac surgery. The aim of our study was to assess the value of targeted cardiac resynchronization therapy (CRT) within 72 hours after cardiac surgery in patients with mechanical dyssynchrony, who had an ejection fraction ≤ 35%, QRS ≥150 ms or between 120 and 150 ms. METHODS: A prospective randomized trial based on three-dimensional echocardiography (RT3DE) and optimized sequential dual-chamber (DDD ) pacing in patients after cardiac surgery. DDD epicardial pacing (Medtronic coaxial epicardial leads 6495) was provided by a modified Medtronic INSYNC III Pacemaker (Medtronic Inc., Minneapolis, MN, USA). SUMMARY OF RESULTS: The study included 21 patients with ischemic heart disease (HD) or valvular HD (16 men, 5 women, average age 69 years) with left ventricle (LV) dysfunction after cardiac surgery . Patients with biventricular (BIV) (CO 6.7 ± 1.7 L/min, CI 3.5 ± 0.8 L/min/m(2) ) and LV (CO 6.2 ± 1.5 L/min, CI 3.2 ± 0.7 L/min/m(2) ) pacing had statistically significantly higher CO and CI than patients with right ventricular (RV) (CO 5.4 ± 1.4 L/min, CI 2.8 ± 0.6 L/min/m(2) ) pacing (BIV vs RV P ≤ 0.001; LV vs RV P ≤ 0.05; BIV vs LV P ≤ 0.05). CONCLUSIONS: RT3DE targeted and optimized CRT in the early postperative period after cardiac surgery provided better hemodynamic results than RV pacing.
Keywords: Echocardiography, Three-Dimensional; Hemodynamics; hemodynamika; Cardiac Resynchronization Therapy; ischemická choroba srdeční; lidé středního věku; výsledek terapie; Ventricular Dysfunction, Left; dysfunkce levé srdeční komory; ženské pohlaví; Myocardial Ischemia; lidé; srdeční resynchronizační terapie; tepový objem; mužské pohlaví; echokardiografie trojrozměrná; senioři; srdeční selhání; Aged, 80 and over; Treatment Outcome; Aged; senioři nad 80 let; Humans; Heart Failure; Heart Valve Diseases; Female; Middle Aged; nemoci srdečních chlopní; Male; Stroke Volume